Measurement of Boundaries and Installation of Boundary Marks for the Function of The Muara Mahat Limited Production Forest in Kampar District, Riau Province - Alexander Ruruh; Muammar Hasan Tuharea; Sarnadi Sarnadi (Yayasan Adra Karima Hubbi, 2024)
Forest areas that remain with permanent boundaries, namely location, location, area and boundaries that are fixed and definite physically in the field and have legal certainty. To achieve certainty of forest areas, forest area confirmation is carried out, through a long process, namely designation of forest areas, boundary arrangement, mapping and determination of forest areas. The purpose of the Functional Boundary Arrangement is to make the Functional Boundary Mark of the Muara Mahat Limited Production Forest Area in Kampar Regency, Riau Province have legal certainty regarding the location, area and boundaries both administratively and physically in the field. The methods used in general are: Observation, is an activity for observing satellite signals to boundary markers in the Muara Mahat Limited Production Forest Area, Kampar Regency, Riau Province. Receiver, to measure auxiliary points or turning points with a distance of approximately 100 meters. The results of the implementation of the Definitive Boundary Arrangement activity in the form of a map with the title